Fluorescence bioanalytical method for urea determination based on water soluble ZnS quantum dots - Safitri, E; Heng, LY; Ahmad, M; Ling, TL (Elsevier Science Sa, 2024)
A new bioanalytical method for urea determination by using the immobilized urease on the highly luminescent ZnS quantum dots (QDs), which functioned as the pH fluorescent label has been developed. Bioconjugation of ZnS QDs to urease via amide bond was performed to obtain the ZnS QDs-urease bioconjugate. Upon enzymatic hydrolysis of urea by the immobilized urease, a pH change to a more alkaline condition has led to the deprotonation of ZnS QDs, and an increase in the fluorescence intensity can be observed. The fluorescence intensity of the urease conjugated ZnS QDs changed linearly with the urea concentrations between 4 x 10(-9) M and 4 x 10(-3) M (R-2 = 0.992) at pH 6 with a calibration sensitivity of 179.46 intensity/decade. No noticeable influence by the Ca2+, Mg2+, K+ and Na+ ions on the response of the fluorescent pH bioprobe. Urea determination in soil sample by using the urea bioprobe was in good agreement with the standard DMAB (p-dimethylaminobenzaldehyde) UV-vis spectrophotometric method. By employing the strategy of ZnS QDs-urease bioconjugation, the stable covalent link between the two substances has appeared to widen the dynamic range and lower the detection limit for urea compared to free enzyme and QDs in solution for bioassay of urea concentration. (C) 2016 Elsevier B.V. All rights reserved.